Introduction to the philosohpy of Leibniz - Latta, Robert (The University of Edinburgh, 1897)
***[This volume has no title page, and commences at Section II: there may be a missing Section I and/or Volume I]***

II. General principles of the philosophy of Leibniz p.1-79 | Notes to Section II

III. Detailed statement of the philosophy of Leibniz p.99[?] A. Leibniz's mathematics in relation to his philosophy p.80-165 B. Ethics p.166-182 | notes to Section III